Two essays on foreign direct investment and financial market development - Scarpa de Mello, Diego (Universidade Federal de São Carlos, 2021)
Current literature states that Foreign Direct Investments (FDI) is able to induce regional entrepreneurship in the host country. However, few studies have evaluated the interplay among FDI and Financial Market Development (FMD) for the creation of firms within the scope of emerging economies. Thus, we present this study in two parts: (i) through a systematic literature review we analyze the relationship between FDI and FMD, to understand the evolution of scientific publications on the subject, in addition to presenting the main results found and suggestions for future work, (ii) by employing a unique database of FDI in Brazil between 2010 and 2014, our studies aim to shed light on aforementioned issue. We analyzed two relevant dimensions of the financial market: credit availability (depth) and banking branches (access) in the same period. Our findings indicate that regions that combine FDI, depth, and access present a higher, positive impact on the number of new firms, which is a relevant policy implication to encourage local business in emerging economies.
Dois estudos sobre investimento direto externo e desenvolvimento do mercado financeiro
Keywords: Foreign direct investment; Financial market development; Firm creation; ENGENHARIAS